Characterization of the molecular properties and allergenicity (IgE-binding capacity) of β-lactoglobulin by heat treatment using asymmetric-flow field-flow fractionation and ultra-performance liquid chromatography quadrupole time of flight mass chromatography. (16th April 2022) - Li, Yang; Yang, Yunjia; Zou, Yue; Shu, Lin; Han, Nan-yin; Yang, Yi
Highlights: β-lactoglobulin (β-LG), after heat treatment (90 °C, 10 min), dissociated and aggregated into four fractions with different molar mass values, sizes and shapes observed from the result of AF4 and TEM. Irregular shape of molecular due to aggregation might be one of the potential reasons of allergenicity enhancement. Peptide LIVTQTMK and some unknown peptides were observed through heat treatment (90 °C, 10 min), while some of β-LG epitope peptides were damaged. Abstract: In this study, the heat product (90 °C, 10 min) of β-lactoglobulin (β-LG) was analyzed by asymmetric-flow field-flow fractionation (AF4) to observe the effect of heat treatment. The changes in molar mass (M) and molar size induced by heat treatment were characterized by AF4, and changes in molar shape were observed by transmission electron microscopy (TEM). The results showed that β-LG dissociated and aggregated into four fractions with different M values, sizes, and shapes after heat treatment. The vast aggregations with the highest allergenicity (IgE-binding capacity) might enhance the allergenicity of β-LG. However, the number of characterized epitope peptides was decreased due to heat treatment. The above results provide some references for related studies of β-LG and its allergenicity. Further separation and characterization of the high-allergenicity fractions and peptides will help to eliminate allergens in dairy products and reduce the occurrence of allergic reactions.